2022
DOI: 10.3390/ma15030794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of V Content and Heat Input on HAZ Softening of Deep-Sea Pipeline Steel

Abstract: In this paper, the welding thermal cycle process of deep-sea pipeline steel was investigated by welding thermal simulation. The microstructure evolution, crystallology and second-phase precipitation behavior of the soft zone of the heat-affected zone (HAZ) were characterized and analyzed by combining scanning electron microscopy, electron back-scattered diffraction, transmission electron microscopy and hardness testing. The results show that HAZ softening appeared in the fine-grained zone with a peak temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The movement speed of the bending test punch is about 1 mm/s. Flexural strength [39] can be determined by the following Equation (1). In this study, the length between two supports is 60 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The movement speed of the bending test punch is about 1 mm/s. Flexural strength [39] can be determined by the following Equation (1). In this study, the length between two supports is 60 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Welding [1,2] is a process of joining materials, which is divided into solid-state and fusion welding. Friction welding (FRW) [3] is a non-fusion welding process that generates heat through mechanical friction between specimens in relative motion.…”
Section: Introductionmentioning
confidence: 99%
“…In general, RFW gives many features based on its practical experience in industry compared with adhesive bonding [2,3]. The RFW process provides a lower peak temperature in the weld joint compared with fusion welding (FW) [4][5][6]. Therefore, a wide range of similar or dissimilar materials can be joined efficiently and economically.…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al [14] suggested that the larger-size polygonal ferrite (PF) and granular ferrite formed from the ununiform prior austenite resulted in softening phenomenon. In order to reduce the HAZ softening, researchers have put forward many methods [15,16]. Dong et al [15] found that increasing the welding heat input could suppress the formation of martensite and reduce the microhardness of HAZ.…”
Section: Introductionmentioning
confidence: 99%
“…The low welding heat input and proper heat-treatment process are the effective way to inhibit the welding HAZ softening. Moreover, Li et al [16] found that the addition of V element was the effective way to retard the softening phenomenon by refining the HAZ microstructure and promoting the nanoscale precipitation of the VC.…”
Section: Introductionmentioning
confidence: 99%